2018
DOI: 10.1182/blood-2018-07-861641
|View full text |Cite
|
Sign up to set email alerts
|

Five-year PFS from the AETHERA trial of brentuximab vedotin for Hodgkin lymphoma at high risk of progression or relapse

Abstract: Key Points Early consolidation with BV improves 5-year PFS vs best supportive care and reduces the need for subsequent therapy. At 5-year follow-up, BV shows long-term tolerability, with peripheral neuropathy continuing to improve and/or resolve.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
187
1
14

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(203 citation statements)
references
References 2 publications
1
187
1
14
Order By: Relevance
“…Patients with high‐risk disease with primary refractory HL or relapse within 12 months of completion of frontline therapy or extranodal involvement at relapse were randomized to up to 1 year of brentuximab given every 3 weeks versus placebo. At 5‐year follow‐up, 59% of patients who received BV were progression free compared with 41% in the control arm . The benefit was most prominent in patients with two or more risk factors: relapse within 12 months or refractoriness to frontline therapy, partial response, or stable disease after most recent salvage therapy, extranodal disease at relapse, B symptoms at relapse, more than two prior salvage therapies.…”
Section: Consolidation After Asctmentioning
confidence: 99%
“…Patients with high‐risk disease with primary refractory HL or relapse within 12 months of completion of frontline therapy or extranodal involvement at relapse were randomized to up to 1 year of brentuximab given every 3 weeks versus placebo. At 5‐year follow‐up, 59% of patients who received BV were progression free compared with 41% in the control arm . The benefit was most prominent in patients with two or more risk factors: relapse within 12 months or refractoriness to frontline therapy, partial response, or stable disease after most recent salvage therapy, extranodal disease at relapse, B symptoms at relapse, more than two prior salvage therapies.…”
Section: Consolidation After Asctmentioning
confidence: 99%
“…As a targeted therapy with a low frequency of severe hematological toxic effects, use of BV might provide a unique opportunity to deliver pre-emptive therapy after ASCT. 9,12,15 This study is quite promising as it reflects the first experience with BV in children with advanced stage RR/HL cases and positive results with respect to the use of BV, especially in early relapsed or refractory HL. In our study, six patients with early relapsed or primary refractory disease that have been treated with BV combined with AVD were able to go into remission.…”
Section: Discussionmentioning
confidence: 66%
“…The aim is to have a consolidation treatment that will prevent the relapse of the disease following ASCT. [10][11][12][13][14] Two randomized trials showed a significant improvement in progression-free survival after ASCT, and several large studies have shown that this procedure can provide a cure in roughly 50% of the patients undergoing ASCT. Various treatment strategies for improving outcomes after ASCT have been investigated, including PET-adapted approaches, intensification of the conditioning regimen, radiation before and after transplantation, and consolidation therapy after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The progression-free survival rate was 82% at 18 months for 28 evaluable patients, an increase from a historical rate of 60% derived from the AETHERA trial, 8 and it met the primary end point. The 18-month overall survival was 100%.…”
mentioning
confidence: 86%
“…However, a significant number of patients will relapse, and the role of BV maintenance is unclear, especially in patients in complete metabolic response (CMR) at the time of transplantation. 7 The posttransplant immune milieu is characterized by a distinct resurgence of immune-effector cells consisting of NK cells, monocytes, and T effector and T memory cells. If harnessed and molded appropriately, the immune engine can be revved up in favor of antitumor immunity.…”
mentioning
confidence: 99%